A connexin30 mutation rescues hearing and reveals roles for gap junctions in cochlear amplification and micromechanics - Victoria A. Lukashkina; Snezana Levic; Andrei N. Lukashkin; Nicola Strenzke; Ian J. Russell (Nature Communications, 2017)
A point mutation in the gap-junction protein connexin 30 stops early onset age-related hearing loss. Here, the authors show that gap junctions contribute to cochlear micromechanics and that cochlear amplification is likely controlled by extracellular potentials in vicinity of the cochlear sensory cells.